How to foster cities resilient to the COVID-19 pandemic through Urban Health strategies. (30th September 2020) - Capolongo, S; Buffoli, M; D'Alessandro, D; Fara, G M; Appolloni, L; Signorelli, C
Abstract: Background: The ongoing pandemic of COVID-19, which nowadays has exceeded 2.5 million notified infections in the world and about 200, 000 deaths, is a strong reminder that urbanization has changed the way that people and communities live, work, and interact, and it's necessary to make the systems and local capacities resilient to prevent the spread of infectious diseases. How we can re-design the concept of Public Health in relation to the built environment and the contemporary cities? Methods: According to the previous statements and scenario, aim of this paper is to integrate the Urban Health strategic objectives, focusing the possible responses, both immediate and medium-long term, to the current environmental, social, and economic aspects of the "period" of physical distancing. Results: Immediate Actions are 01. program the flexibility of city schedules; 02. plan a smart and sustainable mobility network; 03. define a neighborhood services' plan; 04. develop a digitization of the urban context, promoting the smart communities; 05. re-think the accessibility to the places of culture and tourism. Medium-long term Actions are 06. design the indoor flexibility of domestic living spaces; 07. re-think building typologies, fostering the presence of semi-private or collective spaces; 08. renovate the basic care services' network; 09. integrate the existing environmental emergency plans, with those related to the health emergencies; 10. improve stakeholders' awareness of the factors affecting Public Health in the cities. Conclusions: The Decalogue of Public Health opportunities may provide a useful basis for Designers (Architects and Urban Planners), Policy Makers, Public Health experts and Local Health Agencies, in promoting actions and policies aimed to transform our cities in healthier and Salutogenic living environments. Key messages: The strategies described in this paper are at the basis of a social and infrastructural rethinking of the city, careful to the Welfare and Public Health needs. The physical distancing imposed, may have amplified population's social and health inequalities.